Evolving trends in next-generation probiotics: a 5W1H perspective. Issue 11 (16th June 2020) - Almeida, Diana; Machado, Daniela; Andrade, José Carlos; Mendo, Sónia; Gomes, Ana Maria; Freitas, Ana Cristina
Abstract: In recent years, scientific community has been gathering increasingly more insight on the dynamics that are at play in metabolic and inflammatory disorders. These rapidly growing conditions are reaching epidemic proportions, bringing clinicians and researcher's new challenges. The specific roles and modulating properties that beneficial/probiotic bacteria hold in the context of the gut ecosystem seem to be key to avert these inflammatory and diet-related disorders. Faecalibacterium prausnitzii, Akkermansia muciniphila and Eubacterium hallii have been identified as candidates for next generation probiotics (NGPs) with exciting potential for the prevention and treatment of such of dysbiosis-associated diseases. The challenges of these non-conventional native gut bacteria lie mainly on their extreme sensitivity to O2 traces. If these strains are to be used successfully in food, supplements or drugs they need to be stable and active in humans. In the present review, we present an overall perspective of the most updated scientific literature on the newly called NGPs through the 5W1H (What, Why, Who, Where, When, and How) method, an innovative and attractive problem-solving approach that provides the reader an effective understanding of the issue at hand.